Dividend Discount Model Theory Implementation Based On Maqashid Shariah In Indonesia Shariah Stock Market - Masdaliyatul lulukiyyah (Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
Purpose - The purpose of this article is to explore how the use of the Dividend Discount Model (DDM) can be enriched by taking into account the principles of Maqashid Syariah and the economic thinking of Imam Al-Ghazali.Method - This research uses a literature review method with a qualitative descriptive approach. Data was obtained through a study of relevant literature with a focus on the Dividend Discount Model (DDM), the concept of Maqashid Syariah, and the economic thought of Imam Al-Ghazali.Result - The results of the analysis show that the integration of the Dividend Discount Model (DDM) with the Maqashid Syariah concept and Imam Al-Ghazali's economic thinking can provide a more holistic approach and in accordance with Islamic values in evaluating share value in the Islamic capital market. This approach emphasizes the importance of taking into account aspects of social and spiritual benefit, as well as contributing to inclusive and sustainable economic development.Implication - The implication of this research is that the use of the Dividend Discount Model (DDM) which is enriched with the Maqashid Syariah concept and Imam Al-Ghazali's economic thinking can help improve the performance of the Islamic capital market and strengthen compliance with Islamic principles in economic activities. This can have a positive impact on community welfare and sustainable economic development in Indonesia.Originality- The integration of the Dividend Discount Model (DDM) with the Maqashid Syariah concept and Imam Al-Ghazali's economic thinking is an innovation that can increase our understanding of the relationship between religious values and economic practices.